Operations management [videorecording] : a case study of a hotel - Pearce, Mark; Dent, Louisa; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
Service providers are essential in our economy. Where would we be without hospitals, cleaning companies, accounting firms and hairdressers? But it can be difficult to apply concepts of operations management to these businesses. Focusing on the operational processes, this program takes you behind the scenes, learning about the four strategic areas of operations; facilities, materials, quality and technology, applying them to a service provider and showing how various strategies can be used to improve business performance. A great insight into the unique aspects of services marketing.
Voive over: Jane Lundmark
DVD format
Keywords: Marketing -- Management; Operations management; Hotel Management -- Case studies; Service industries -- Marketing -- Management